Religious Expressions of the Qur'an in the Poem “Awhamun fī Zaitun” by Fadwa Tuqan - Sunaryo, Marsel Nurhaliza; Liza, Fitri (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to explore Fadwa Tuqan's religious expression by examining the relationship between the Qur'an and the poem “Awhamun Fiy Zaitun” through Julia Kristeva's intertextual approach. The focus of this study is on how the poet expresses her religiosity in her poetry. The method used is a descriptive, qualitative method with content analysis techniques designed for library research. The data are analyzed to identify patterns of intertextuality, expressed as intertextual principles, that connect the two texts: poetry and the Qur’an. The results of this study found that Fadwa Tuqan absorbed elements of the Qur'an into the poem “Awhamun Fiy Zaitun”  through the principles of dominant transformation, modification, expansion, defamiliarization,  existence and excerpts so that the symbol زيتون became the basis for the title of this poem. This reflects the expression of religiosity as a Muslim in Palestine who makes the Qur'an the source of her religiosity. Overall, this study provides insight into the creative relationship between sacred texts and Tuqan's poetry. The implications enrich modern Arabic literature as a metaphysical dialogue with God and provide a theoretical and practical contribution to the study of Palestinian poetry.